Consumerism and its Relation to Self -Identity: A Field Study on the Students of the University of Jordan - Abu Zaghlan, Majd; Al-Wraikat, Ayed (Dirasat: Human and Social Sciences, 2022)
The study aims at identifying the relation between consumerism and the self identity. For this purpose, a questionnaire was designed as the study tool and consisted of two parts; the first part comprised of the demographic data whereas the second one comprised of a measurement scales of the consumerism (four-dimension scale) and self identity (one-dimension scale). On a theoretical level, this study considered some of the assumptions of Zygmunt Bauman’s work, especially “Liquid Modernity” theory. The social survey method was used and applied to an organized random sample from the students of the University of Jordan. Descriptive statistics, analysis of variance, correlation, T-test and the multi-regression test were used. The study concluded that the sample subjects scored an average level for each of the cultural dimension, subjective dimension, and symbolic dimension of consumerism. However, the social dimension scored a low level. The study revealed that the sample subjects had high level of self identity. The independent variable (consumerism) interprets (0.026) of the variables occurring in the dependent variable (self identity). There was negative correlation between the consumerism in its subjective dimension and the self identity that resulted in reduced identification of the self identity. It was revealed that the symbolic dimension of consumerism is the second reason for the changes affecting the self identity; in fact, there was a positive correlation between them. However, the other dimensions of consumerism were not statistically significant.